Pengaruh Lama Fermentasi dengan Lactobacillus plantarum terhadap Karakteristik Fisikokimia dan Fungsional Tepung Biji Durian (Durio zibethinus Murr) - Widhiastiti, Ni Putu Ulfi; Trisna Darmayanti, Luh Putu; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This research was aimed to determine the effect of fermentation time on the physicochemical and functional characteristics of fermented durian seed flour using Lactobacillus plantarum inoculum. This study used a completely randomized design with fermentation time treatment consisting of 5 levels, namely: 0 hours, 12 hours, 24 hours, 36 hours, and 48 hours. Each treatment was repeated 3 times in order to obtain 15 experimental units. Data were analyzed by analysis of variance and if the treatment had a significant effect, it the variables, it was continued with Duncan's Multiple Range test. The results showed that the fermentation time had a significant effect on yield, density of Kamba, oil absorption capacity, solubility and total lactic acid bacteria, but had no significant effect on moisture content, ash content, color density, water absorption capacity, and swelling power. Long treatment of fermentation with a time of 48 hours resulted in the best fermented durian seed flour with the characteristics of ash content of 0.67%, moisture content of 9.87%, density of kamba 0.49%, color density L 34.59, starch content, water absorption capacity 1,95%, oil absorption capacity 2.41, swelling power 45.01%, solubility, 24.30% total LAB.